The Use of Radiation and How to Prevent Risk - Mustafa Nadel Ahmed Rady; Mohammed Abd Ali Jabi Ratib; Yahya Abbas Kazem Shanan; Haneen Aqeel Latif Qsm; Soror Alaa Ghani Marzouk (Genius Journals, 2024)
Radiation is a broad term that includes electromagnetic rays (photons), charge-free particles such as neutrons, and charged particles, whether positive such as protons and alpha particles or negative such as beta particles and negative ions. Radiation in general can be harmful. Electromagnetic rays include radio waves, whose wavelength reaches about 3 km, infrared rays, visible light, ultraviolet rays, and. The danger of radiation lies in the fact that it causes many injuries and diseases to humans and other organisms, especially cancerous diseases as well as hereditary diseases. There are more than forty sites throughout Iraq that are polluted with high levels of ionizing radiation and toxic substances. The environmental pollution caused by nuclear and electromagnetic radiation affects all aspects of human life. Animals and plants together, and its effects cannot be limited to a short-term period of time, which has made it a global problem that countries have been exposed to at the regional and international levels, searching for ways to curb its dangers and to stand up to the excessive escalation in radiation emissions, which has increased with the spread of the use of technologies
Keywords: radiation; harms of radiation; uses of radiation